2019
DOI: 10.1038/s41598-018-35988-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Fixed-bed Flow Reactions under Microwave Irradiation by Local Heating at the Vicinal Contact Points of Catalyst Particles

Abstract: The formation of local high temperature regions, or so-called “hot spots”, in heterogeneous reaction systems has been suggested as a critical factor in the enhancement of chemical reactions using microwave heating. In this paper, we report the generation of local high temperature regions between catalyst particles under microwave heating. First, we demonstrated that reaction rate of the dehydrogenation of 2-propanol over a magnetite catalyst was enhanced 17- (250 °C) to 38- (200 °C) fold when heated with micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…Regarding the non-thermal effects, the calculations proved that properties such as the polarizability of transition states and the stabilization of radicals and triplet state influence the reactivity by means of non-thermal effects. In the case of fixed bed flow reactors, an interesting study was carried out by Haneishi et al [28], whose studies allowed to conclude that the generation of local heating at the contact points between the catalyst particles is a key factor for enhancing fixed-bed flow reactions under microwave irradiation. The authors, in the case of the dehydrogenation of 2-propanol over a magnetite catalyst, reported the generation of local high temperature regions between catalyst particles under microwave heating.…”
Section: Microwave Heating Applications In Heterogeneous Catalysismentioning
confidence: 99%
“…Regarding the non-thermal effects, the calculations proved that properties such as the polarizability of transition states and the stabilization of radicals and triplet state influence the reactivity by means of non-thermal effects. In the case of fixed bed flow reactors, an interesting study was carried out by Haneishi et al [28], whose studies allowed to conclude that the generation of local heating at the contact points between the catalyst particles is a key factor for enhancing fixed-bed flow reactions under microwave irradiation. The authors, in the case of the dehydrogenation of 2-propanol over a magnetite catalyst, reported the generation of local high temperature regions between catalyst particles under microwave heating.…”
Section: Microwave Heating Applications In Heterogeneous Catalysismentioning
confidence: 99%
“…Significant efforts have been made to demonstrate the impact of microwave irradiation on thermal and catalytic chemical reactions in contrast to conventional processes. The key conclusions of these efforts include the noticeable improvements of microwaves on conversion, product yield and quality, energy consumption, and reaction rate among other aspects . However, the impact of this energy conversion mechanism on reaction kinetics, in particular activation energies and molecular mobility, is still undocumented.…”
Section: Microwave Heating Challenges and Controversial Issuesmentioning
confidence: 99%
“…Applying conventional heating in this type of reaction requires quenching or fast cooling the products to avoid undesirable further decompositions. Haneishi et al have demonstrated the temperature distribution of packed catalyst particles under microwave irradiation using the finite element method . Taking advantage of the enormous interaction between microwaves and active catalytic agents in this reaction and the low response of the produced gases to the microwaves can selectively enhance the reaction in a noticeable way.…”
Section: Prospective Microwave Applicationsmentioning
confidence: 99%
“…Microwave (MW) heating processes have been applied to a lot of catalytic reactions [1][2][3][4][5][6][7][8]. In the heterogeneous gas-solid system, solid catalysts are selectively heated due to the interactions of the conduction electrons or the dipoles with MWs [1].…”
Section: Introductionmentioning
confidence: 99%